2013
DOI: 10.1038/bonekey.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

Variation in type I collagen fibril nanomorphology: the significance and origin

Abstract: Although the axial D-periodic spacing is a well-recognized nanomorphological feature of type I collagen fibrils, the existence of a distribution of values has been largely overlooked since its discovery seven decades ago. Studies based on single fibril measurements occasionally noted variation in D-spacing values, but accredited it with no biological significance. Recent quantitative characterizations supported that a 10-nm collagen D-spacing distribution is intrinsic to collagen fibrils in various tissues as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 72 publications
5
44
0
Order By: Relevance
“…It could be considered that this variation in the periodic spacing is intrinsic to the collagen type I self-assembly process, because of local changes in the mechanical stresses. Those changes are due to the variations in the intra-brillary interactions, including hydrophobic and electrostatic interactions, hydrogen bonds and crosslinks in hydroxylysine and hydroxyprolines [34]. Each bril diameter is between 450 and 550 nm, which coincides with the reported value for the tendons brils that are up to 1 cm long and 500 nm in diameter [35].…”
Section: Discussionsupporting
confidence: 80%
“…It could be considered that this variation in the periodic spacing is intrinsic to the collagen type I self-assembly process, because of local changes in the mechanical stresses. Those changes are due to the variations in the intra-brillary interactions, including hydrophobic and electrostatic interactions, hydrogen bonds and crosslinks in hydroxylysine and hydroxyprolines [34]. Each bril diameter is between 450 and 550 nm, which coincides with the reported value for the tendons brils that are up to 1 cm long and 500 nm in diameter [35].…”
Section: Discussionsupporting
confidence: 80%
“…6,7 Recent AFM studies indicated changes in the nanomorphology of the Type I collagen fibrils in ovariectomized (OVX) sheep [8][9][10] and rats. 11 In order to explore the effect of estrogen depletion and compare efficacy of CatKI and alendronate (ALN) drug treatments, the rabbit OVX model was developed by Merck Inc., as human CatKI's exhibit similar potency for the rabbit enzyme and the adult rabbit skeleton undergoes substantial cortical Haversian remodeling (unlike the rodent).…”
Section: Resultsmentioning
confidence: 99%
“…Collagen from different tissues undergo a series of unique post‐translational modifications that will govern the spatial organization, diameter, cross‐linking, and D‐spacing of the collagen fibrils (Fang & Holl, ). In addition, the processing conditions, such as temperature, pH, ionic strength, enzyme treatment, and the initial raw material, are known to influence collagen functional properties such as gelation rate, viscosity, and water retention capacity (Schmidt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, collagen cultures and specifically human collagen led to reduced expression of chemokines and pro-inflammatory cytokines but caused concomitant higher expression of immunomodulatory factor; such tuned MSC profile could be beneficial when administered to inflamed myocardium. Collagen from different tissues undergo a series of unique posttranslational modifications that will govern the spatial organization, diameter, cross-linking, and D-spacing of the collagen fibrils (Fang & Holl, 2013). In addition, the processing conditions, such as temperature, pH, ionic strength, enzyme treatment, and the initial raw material, are known to influence collagen functional properties such as gelation rate, viscosity, and water retention capacity (Schmidt et al, 2016).…”
Section: Global Analysis Of Protein Deposition and Degradationmentioning
confidence: 99%